Nguyễn Thanh HằngNguyễn Thị Hồng NhungToshiro Kiyoshi
Bài 2:
\(x^3+y^3+z^3-3xyz\)
\(=\left(x+y\right)^3+z^3-3x^2y-3xy^2-3xyz\)
\(=\left(x+y+z\right)\left[\left(x+y\right)^2-\left(x+y\right)z+z^2\right]-3xy\left(x+y+z\right)\)
\(=\left(x+y+z\right)\left[\left(x+y\right)^2-\left(x+y\right)z+z^2-3xy\right]\)
\(=\left(x+y+z\right)\left(x^2+2xy+y^2-xz-yz+z^2-3xy\right)\)
\(=\left(x+y+z\right)\left(x^2+y^2+z^2-xy-xz-yz\right)\)
Chúc bạn học tốt!!!
Bài1:
\(\left(x^4-x-14\right):\left(x-2\right)=x^3-2x^2-4x+7\)
Bài2:
Toshiro Kiyoshi làm r nhé